Ex-Utero Intrapartum Treatment-to-Airway for Obstructing Fetal Neck Masses: A Singular Methodology for Monochorionic and Dichorionic Twin Pregnancies - Papastefan, Steven T.; Scorletti, Federico; Alhajjat, Amir M.; Ott, Katherine C.; Rastatter, Jeffrey C.; Pombar, Xavier F.; Shaaban, Aimen F. (American Journal of Perinatology Reports, 2023)
Fetal airway obstruction in one twin of a diamniotic pregnancy presents unique challenges. Very few cases of ex-utero-intrapartum-treatment (EXIT) procedures for twin pregnancy have been reported and only in dichorionic pregnancies. We report a singular methodology for EXIT-to-airway procedures in two pregnancies involving monochorionic and dichorionic twins.Two cases of EXIT-to-airway in twin pregnancies were performed in 2018 and 2019 at a regional fetal treatment center. Case 1 involved a giant cervical teratoma in a monochorionic-diamniotic twin pregnancy with preterm labor at 29 weeks. Case 2 involved a dichorionic-diamniotic pregnancy with a large cervical lymphatic malformation with preterm labor at 36 weeks. In each case, the polyhydramnios caused the affected twin's amniotic sac to be the presenting sac for the surgical approach. Bronchoscopy and successful intubation was completed after 22 and 10 minutes of uteroplacental bypass, respectively. The bystander twins were delivered second without intubation and resuscitated without perinatal distress.EXIT-to-airway appears to be a reasonable option for twins including monochorionic pregnancies, via delivery of the affected twin first followed by delivery of the bystander twin. Thoughtful preparation and counseling by an experienced multidisciplinary team permits an EXIT-to-airway approach for twin pregnancies even in an emergent setting.
Keywords: EXIT-to-airway; fetal neck mass; monochorionic; dichorionic; lymphatic malformation; cervical teratoma; twin pregnancy; airway obstruction